PENDAMPINGAN IMPLEMENTASI PERTANIAN CERDAS IKLIM DI KECAMATAN GEBANG KABUPATEN CIREBON - Yeti; Euis Dasipah; Sri Ayu Andayani; Nendah Siti Permana; Tuti Gantini (Universitas Majalengka, 2022)
Agriculture is one of the important sectors of human life, especially in food commodities. Still, problems in this sector continue, climate change is difficult to predict, increases in pests and diseases, and so on. Many farmers today use chemical fertilizers and pesticides. Counseling on the implementation of climate-smart agriculture in the Karya Mukti III farmer group, Dompyong Kulon Village Gebang, Cirebon is the theme of community service activities. The purpose and objective of this activity are to provide understanding to farmers as an alternative option and the potential to be developed from climate-smart agriculture. The method in this activity is an approach to counseling, education, lectures, and discussion methods. This activity resulted in the understanding of farmers in implementing climate-smart as an alternative to reducing farmers' dependence on chemical fertilizers and pesticides, with interactive discussions between farmers.